2021
DOI: 10.3390/ijerph182212175
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Predict the Level of Substance Craving of People with Drug Addiction: A Machine Learning Approach

Abstract: This study aimed to explore which factors had a greater impact on substance craving in people with substance use and the direction of the impact. A total of 895 male substance users completed questionnaires regarding substance craving, psychological security, positive psychological capital, interpersonal trust, alexithymia, impulsivity, parental conflict, aggression behavior, life events, family intimacy, and deviant peers. Calculating the factor importance by gradient boosting method (GBM), found that the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Numerous studies have shown a high level of ,anxiety, and aggression in people with relapse. , A low level of interpersonal trust and insecurity, A low level of interpersonal trust and insecurity, predicts a high level of anxious and aggressive behavior [23], [24]. Chauhan, Nautiyal, Garg, and Singh research to find out predictors of relapse in cases of opioid/alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown a high level of ,anxiety, and aggression in people with relapse. , A low level of interpersonal trust and insecurity, A low level of interpersonal trust and insecurity, predicts a high level of anxious and aggressive behavior [23], [24]. Chauhan, Nautiyal, Garg, and Singh research to find out predictors of relapse in cases of opioid/alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China suggests that low self-efficacy predicts relapse in drug addiction. The relationship between the individuals who face relapse and their blood relations should be raised, and the rehabilitation center should take various measures to improve the psychological capital level and the level of self-awareness of the people who frequently use drugs, and it will be helpful to reduce their relapse rate [16].…”
Section: International Scenariosmentioning
confidence: 99%
“…The literature work discussed various applications of classi cation algorithms and machine learning techniques in various elds such as medical diagnosis[6]-[8], substance abuse [9], and diabetes[6], [8], [10], [11] prediction. In the study [12], authors used anthropometric data and blood analysis parameters to classify patients with breast cancer using arti cial neural networks and Naive Bayes classi ers, with high potential for accurate diagnosis.…”
Section: Ict In Medicinementioning
confidence: 99%
“…In the study [12], authors used anthropometric data and blood analysis parameters to classify patients with breast cancer using arti cial neural networks and Naive Bayes classi ers, with high potential for accurate diagnosis. The psychosocial factors [9] such as life events, aggression behavior, and interpersonal trust have a greater impact on substance craving in male substance users. The authors in [10] introduced a new labeled diabetes dataset from Bangladesh and proposed an automated classi cation pipeline using a weighted ensemble of machine learning classi ers, which produced the best results for early diabetes prediction.…”
Section: Ict In Medicinementioning
confidence: 99%
“…Psychosocial factors are multidimensional constructing, encompassing two different domains as psychological domain (depression, anxiety, distress, self-esteem, and satisfaction) and the social domain (socioeconomic status, employment, religion, physical attributes, family, relationship with others, locality). These factors contribute to the development of mental and physical disorders [12], [13]. Psychosocial factors influence an individual psychologically or socially.…”
Section: Introductionmentioning
confidence: 99%